Manajemen Kepemimpinan dalam Konsep Manajemen Mutu Terpadu di Sekolah Berstandar Internasional - Debora Pratiwi Sibarani (Program Studi Manajemen Pendidikan, 2023)
Strong leadership is the crucial foundation in creating an effective school management. Leaders in international schools in particular face different challenges because they must be aware of social and cultural contexts in Indonesia. Moreover, the leader must also understand the work ethics of teachers and staff who come from different countries to achieve total quality management in which supports the school organization. This study aims to provide a clear framework for leadership management in the context of international schools in Indonesia using qualitative research methods. The discussion in this study uses the results of observations by referring to the appropriate literature reviews regarding the strategies for achieving total quality management in schools. The result of the study shows that total quality management can be achieved because school leaders perform their roles, committed to their tasks, and responsible in making continuous improvements for the benefit of all stakeholders.